2006
DOI: 10.1002/ecjc.20277
|View full text |Cite
|
Sign up to set email alerts
|

Research on routing consistency in the Internet routing registry

Abstract: SUMMARYAn IRR (Internet Routing Registry) is a database for registering routes on the Internet or AS numbers. However, there are indications that the data recorded in the IRRs are not correctly updated and do not correctly reflect the actual situation on the Internet. Accordingly, this research evaluated (1) the consistency of IRRs with actual Internet routing information and (2) differences in consistency among IRRs. Specifically, route objects in an IRR and actual BGP routing information were compared using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It is also recommended by network governance organizations such as MANRS [48] because of its extensive coverage and expressiveness. However, the issues of IRR regarding its staleness have been raised multiple times [41], [34], [50], [18]. For example, Du et al [18] quantifies the consistency between Route and ROA objects using IRR databases collected a monthly granularity and reported that 20% of Route in RADb are covered by ROA objects and only 38% of them are consistent with ROA objects as of October 2021 14 .…”
Section: B Efforts To Sanitize Interdomain Routing Informationmentioning
confidence: 99%
“…It is also recommended by network governance organizations such as MANRS [48] because of its extensive coverage and expressiveness. However, the issues of IRR regarding its staleness have been raised multiple times [41], [34], [50], [18]. For example, Du et al [18] quantifies the consistency between Route and ROA objects using IRR databases collected a monthly granularity and reported that 20% of Route in RADb are covered by ROA objects and only 38% of them are consistent with ROA objects as of October 2021 14 .…”
Section: B Efforts To Sanitize Interdomain Routing Informationmentioning
confidence: 99%